Leadership And Human Development For Nation Building - Adesola Adebayo Akande, Sabitu Olalekan Owotutu Adegbite Ganiu Adewale (International Journal of Scientific Research and Management (IJSRM), 2015)
This paper focussed on how leadership and human development programme could be harnessed for nation building and national development. And considered our present knowledge and practices regarding the sequencing of reform and modernisation efforts, and therefore to shift our emphasis towards a model that offers an ability to adopt, utilise, optimise and further develop the results of development projects. It was revealed that some parameters are central to the development process, particularly strengthening the ability of key individuals to lead, drive, manage, monitor and follow up the efforts to reform and modernise. Leadership is the crown jewel in this respect, since without strong leadership, there will be no development, and without development, no reform, no modernisation and no nation will be buil